2014
DOI: 10.1583/13-4527r.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Infrainguinal Chronic Total Occlusions Using the TruePath Device: Features, Handling, and 6-Month Outcomes

Abstract: TruePath facilitated successful crossing of infrainguinal CTOs following an unsuccessful guidewire recanalization, with significant improvement in symptoms and no complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…This is utilized to drill through a CTO, ideally finding microchannels, as it traverses the CTO. 39 Finally, the Viance™ catheter (Covidien, Minneapolis, MN) is analogous to the CrossBoss™ catheter (Boston Scientific, Marlborough, MA), and is composed of a stainless steel catheter with a rounded-tip. This is utilized with a Fast-spin™ device to rotate the catheter as it advances through CTOs.…”
Section: Revascularization In Dmmentioning
confidence: 99%
“…This is utilized to drill through a CTO, ideally finding microchannels, as it traverses the CTO. 39 Finally, the Viance™ catheter (Covidien, Minneapolis, MN) is analogous to the CrossBoss™ catheter (Boston Scientific, Marlborough, MA), and is composed of a stainless steel catheter with a rounded-tip. This is utilized with a Fast-spin™ device to rotate the catheter as it advances through CTOs.…”
Section: Revascularization In Dmmentioning
confidence: 99%
“…Vascular calcification visible on angiographic views prior to contrast injection was classified as mild (isolated foci of calcification), moderate (contiguous segments of calcification on one or alternating sides of the vessel), or severe (contiguous calcification on both sides of the vessel). [7][8][9][10] …”
Section: Definitionsmentioning
confidence: 99%
“…Technical descriptions of these approved devices have previously been published. 7,8,11 Endpoints and Definitions Outcome measures included crossing success, procedure success, complications, and major adverse events (MAEs). Crossing success was defined as placement of a guidewire in the distal true lumen, past the distal CTO cap, confirmed by either angiography or intravascular ultrasound (IVUS).…”
Section: Strategies and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several previous comparative studies were limited by operator experience and small samples sizes, so results may not necessarily reflect those in daily clinical practice. 4,6,7 The application of intravascular ultrasound (IVUS) for EVT evaluation is also growing. 8 A previous report evaluating intraluminal wire crossing of CTOs with IVUS assessment found that the proportion of plaque crossings (relative to total route distance) may affect primary patency.…”
Section: Introductionmentioning
confidence: 99%